Incorporating preventive maintenance into the m-machine no-wait flow-shop scheduling problem with total flow-time minimization: a computational study. Issue 4 (3rd April 2019) - Miyata, Hugo Hissashi; Nagano, Marcelo Seido; Gupta, Jatinder N. D.
ABSTRACT: In this article, the impact of preventive maintenance policies on the constructive heuristics performance for the no-wait flow-shop problem with total flow-time minimization is evaluated. The main constructive heuristics for the m -machine no-wait flow-shop scheduling problem with total flow-time minimization are compared through computational experiments with a set of 5760 problems. The results show that the adopted parameters significantly affect the performance of the constructive heuristics; also, the computational effort required to solve the problems increases owing to the complexity of the function-objective calculation. Heuristics proposed by Laha and Sapkal (LSH) and Framinan, Nagano and Moccellin (FNMH) provide the best solutions for both evaluated policies.